1999
DOI: 10.1002/(sici)1097-4652(199912)181:3<455::aid-jcp9>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of myofibrillar protein degradation and expression of mRNA encoding the ubiquitin-proteasome system in C2C12 myotubes by dexamethasone: effect of the proteasome inhibitor MG-132

Abstract: Addition of the synthetic glucocorticoid, dexamethasone (Dex) to serum-deprived C(2)C(12) myotubes elicited time- and concentration-dependent changes in N(tau)-methylhistidine (3-MH), a marker of myofibrillar protein degradation. Within 24 h, 100 nM Dex significantly decreased the cell content of 3-MH and increased release into the medium. Both of these responses had increased in magnitude by 48 h and then declined toward basal values by 72 h. The increase in the release of 3-MH closely paralleled its loss fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
15
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 42 publications
4
15
0
Order By: Relevance
“…In muscle cell cultures, the amount of N -methylhistidine released into the medium, as an index of myofibrillar protein degradation, was increased by serum deprivation 36) and glucocorticoid treatment. 37) In this study, AICAR induced the release of N -methylhistidine into the medium from C2C12 myotubes (Fig. 2B).…”
Section: Discussionsupporting
confidence: 54%
“…In muscle cell cultures, the amount of N -methylhistidine released into the medium, as an index of myofibrillar protein degradation, was increased by serum deprivation 36) and glucocorticoid treatment. 37) In this study, AICAR induced the release of N -methylhistidine into the medium from C2C12 myotubes (Fig. 2B).…”
Section: Discussionsupporting
confidence: 54%
“…The catabolic effects of glucocorticoid on overall muscle protein metabolism are well known. For example, glucocorticoid increased overall protein degradation in rat L8 and L6 myotubes and enhanced the degradation of myofibrillar proteins in C2C12 myotubes (1)(2)(3). In response to fasting, muscles of adrenalectomized animals, unlike normals, are unable to increase protein breakdown, whereas complete restoration occurs after glucocorticoid administration.…”
mentioning
confidence: 99%
“…In response to fasting, muscles of adrenalectomized animals, unlike normals, are unable to increase protein breakdown, whereas complete restoration occurs after glucocorticoid administration. mRNA levels for several components of the ubiquitin system are up-regulated by glucocorticoids (2,(4)(5)(6). For example, muscle-specific E3 ligases Atrogin-1/MAFbx and Murf1 were both up-regulated upon glucocorticoid administration to skeletal muscle (4).…”
mentioning
confidence: 99%
“…Previous studies have demonstrated that 3-MH cannot be reutilized for protein synthesis, and therefore, the output of 3-MH has been used as an index of myofibrillar protein degradation [21,27,28] . The concentration of 3-MH was measured as previously described [27,28] .…”
Section: Measurement Of the Surface Area Of Cardiomyocytesmentioning
confidence: 99%